Diferenças individuais no temperamento de crianças pré-escolares e sua associação com habilidades cognitivas - Mariana Teles Santos (2010)
This research looked for a preschools temper assessment based in the Hans Eysencksmodel of the three superfactors and the examination of the association between the tempers dimensions and the cognitives skills measured. The sample was formed by 192 children from 4 to 6 years old (M = 4,58; DP = 0,69), being 108 (56%) feminine person and 85 (44%) masculine person. To evaluate the temper, the research hasconstructed a hetero-report questionnaire, wich was responded by the mothers, presenting appropriate psychometric properties: the Cronbahs alfa scales alternated from 0,77 to 0,90 and the exploratory factorial analysis extracted three factors with eigenvalue upper than one, wich explained 56% of the total variance that indicates a equivalence between the theoretical factorial structure and the structure observed in thisresearch.With the purpose to make a validy convergent study to the psychoticism factor from the tempers questionnaire were used two scales from the Attention Deficit Hyperactivity Disorder Scale (ETDAH) instrument, wich are the Anti-Social Behaviors scale and the Hyperactivity/Impulsivitys scale. The Pearsons correlation analysispresented positive and moderate correlation values, indicating a satisfactory convergence among the factors. To evaluate the cognitive skills, the children did the THCP that evaluated language skills, attention, memory and quantitative thought. Was not found significative correlations between the tempers characters and the cognitive habilititys evaluated, hut, there was a negative correlation among the Anti-Social Behavior and the THCPs total score (r = - 0,193; p < 0,05) and the Language subtest (r= -0,213; p < 0,009). Also, was found a negative correlation between theHiperactivity/Impulsivity scale with the Quantitative Thought from the THCP (r = - 0,207; p < 0,008. This result indicates a commitment in the childrens cognitive performance with anti-sociability characters and self-control absence. Concluded by the replicability of the Eysencks personality model in preschool age zone children, as wellas the children temper evaluation importance in view of its several spheres influence in the life of each person.